The impact of changes in temperature trends on relative humidity trends in the city of Jeddah in Kingdom of Saudi Arabia for the period from 1985 to 2022 AD - Al-Anazy, Jamila Awad; Al-Jasser, Lameah AbedAl-Aziz (Journal of natural sciences, life and applied sciences, 2024)
The current study aims to analyze the change in the trends of both the annual averages of temperature and the annual averages of relative humidity and the effect of temperature trends on the trends of relative humidity at the Jeddah station in the Kingdom of Saudi Arabia for the period from (1985 to 2022 AD), using the method of statistical and cartographic analysis by applying averages methods. Moving averages, averages, simple linear regression, t-test for the statistical significance of the difference between the averages and the statistical significance of the regression equation model. The results showed that the annual averages of temperature took an increasing trend over time, while the annual averages of relative humidity showed a decreasing trend, and this is consistent with what other studies have found in various parts of the world. The results of the study also confirmed the existence of a moderately strong inverse relationship between the changing trends of annual average temperatures and relative humidity at the study station.